(untitled) (Marketing Journal, 2025)
This study provides an in-depth examination of the conceptual and methodological foundations of strategic management of investment flows aimed at mitigating interregional socio-economic disparities. In the context of Uzbekistan, regional economic imbalances, uneven distribution of investment resources, and disparities in economic activity directly influence the sustainability of national growth dynamics. Therefore, the paper explores the potential of integrating digital governance, indicator-based analytical systems, and strategic modeling mechanisms into the regulation of investment flows to reduce territorial inequalities. Based on theoretical analysis, empirical evaluation, and panel data modeling, the study develops a composite approach termed the Balanced Investment Governance Model (BIGM). This model is designed to assess investment efficiency, reallocate resources, and accelerate convergence in regional development rates. The results demonstrate that when strategic governance mechanisms are harmonized with digital indicators and differentiated investment policies, the level of interregional inequality can be substantially reduced.